Enhancing Access to Finance for EAC Women Cross-Border Traders - World Bank (World Bank, Washington, DC, 2021)
This report was commissioned by the World Bank Group’s (WBG) financial inclusion support framework program, with financial support from the Ministry of Foreign Affairs of the Netherlands and the Bill and Melinda Gates Foundation and with technical support from the East African Business Council to provide a diagnostic assessment of the women cross-border trade landscape across the East African Community (EAC). The diagnostic study identified policy and firm-level barriers that limit women’s bankability and financial access generally and during the current Coronavirus disease 2019 (COVID-19) pandemic. The objective of this study is to understand the constraints women cross-border traders in the EAC face in accessing finance and carrying out their operations. The study aims to draw insights from prior research, focus-group discussions (FGDs) with women cross-border traders, key stakeholder interviews, and data requests from commercial banks. This report is structured as follows: chapter one gives introduction. Chapter two describes the approach employed for the research; chapter three summarizes the macroeconomic, sociodemographic, and micro, small, and medium-sized enterprise (MSME) landscape of the partner states; chapter four breaks down the structure of trade across the EAC countries; chapter five provides the demand-side findings; chapter six details the supply-side findings; and chapter seven summarizes the key recommendations. Chapter eight includes annexes, including an East African Business Council (EABC) brief on the impact of COVID-19 on the EAC as of April 24, 2020.